Breast Cancer 2022
DOI: 10.36255/exon-publications-breast-cancer-lymphedema
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Breast Cancer-Related Lymphedema

Abstract: Breast cancer-related lymphedema (BCRL) presents as swelling in the arm, hand, trunk, or breast at varying times after completion of breast cancer treatment. The reported incidence of BCRL varies widely in part due to its dependence on the type and extent of the treatment, pre-treatment risk factors, and the criteria used to define its presence. Central to this issue are the various quantitative measures that are used to specify lymphedema thresholds for its detection and tracking over time and during treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 113 publications
(85 reference statements)
0
23
0
Order By: Relevance
“…These processes can significantly influence target gene expressions. To address such complexity, we modeled individual gene expressions using an autoregulatory gene circuit widely used for modeling various biochemical processes ( Figure 3a ) [30, 31], which is exemplified by an ER-related signaling pathway ( Figure 3b ) [32-35]. This model operates under the assumptions that all genes are controlled by positive and negative feedback mechanisms, and the strength of this feedback control is determined by the mRNA levels and interactions among intracellular signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes can significantly influence target gene expressions. To address such complexity, we modeled individual gene expressions using an autoregulatory gene circuit widely used for modeling various biochemical processes ( Figure 3a ) [30, 31], which is exemplified by an ER-related signaling pathway ( Figure 3b ) [32-35]. This model operates under the assumptions that all genes are controlled by positive and negative feedback mechanisms, and the strength of this feedback control is determined by the mRNA levels and interactions among intracellular signals.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis revealed that 664, 558, and 680 genes exhibited multistability in C1, C3, and C4 subpopulations, respectively ( Figure 4a ). Notably, RPS6KB1 , a predictor of poor prognosis, cell survival, and growth in ER-positive breast cancers [40], exhibited bistability in both C1 and C4, implying that its low and high expression levels are regulated by a binary switch governing distinct cell fates.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recently, Bliss et al showed the importance of Ki67 in treatment decision or in clinical trials when assessing a new treatment [43]. In this study, we opted to classify them based only on the express of HRs either both (luminal A) or 1 especially for luminal B and the absence of HER2 [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…HER2-positive cells express HER-2 receptors and nearly 20% of all breast cancer cells over-express the HER2 protein and are thus optimally treated using drugs such as trastuzumab after chemotherapy to prevent a rebound of the disease. Triple positive breast cancer cells express ER and/or PR, and HER-2 receptors while triple negative cells do not express any of the 3 receptors [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, previous studies classified both luminal groups A and B focusing on the fact that Ki 67 is lowly express or highly expressed (<14 or >14; <20% or >20) [12,14,15]. We opted to classify them based on the express of HRs either both (luminal A) or 1 especially for luminal B and the absence of HER2 [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%